Democracy and the demographic transition. Issue 4 (7th June 2017) - Wilson, Ben; Dyson, Tim
ABSTRACT: This article addresses the role of demographic factors in contributing to the emergence of democracy. It maintains that, other things being equal, progress in the demographic transition promotes democratization. The argument is developed with reference to the effects of interrelated changes in mortality, natural increase (i.e. population growth), fertility, and population age structure. Suggestions are also made with respect to how demographic and democratic trends should be gauged. An analysis of data for the period 1970–2005 for 77 countries that were initially non-democratic provides substantial support for the argument. Some implications are discussed, as are future trends in democratization from a demographer's perspective.